Accounting Students’ Academic Performance by Their Background Information - Sari, Siti Antika; Suryani, Ani Wilujeng (Jurnal Ilmu Pendidikan, 2020)
This study aims to determine differences in academic performance of accounting students by their background information. This study involved secondary data from 810 accounting students, analyzed by using Kruskal Wallis test to investigate differences on gender, living environment and funding source. The results show that the academic performance of female students who live at home and obtain scholarship are better than other groups. However, males who live at home and obtain scholarship have indifferent academic performance from other male groups. These findings indicate that gender, living environment and type of educational funding can be taken into consideration to differentiate students’ academic performance. The results of this study can be used by universities to make decisions in determining acceptance criteria, to identify potential students to increase academic performance, and to resolve problems of underperformed students. This research provides an evidence that females and males have different academic performance. Moreover, we found that females who obtained scholarship maintain their high performance, while males are indifferent in their academic performance irrespective of their source of funding